Activatable sonoafterglow nanoprobes for T-cell imaging - Xu, Cheng (2023)
Real-time imaging of immune systems benefits early diagnosis of disease and precision immunotherapy; however, most existing imaging probes either have "always-on" signals with poor correlation to immune responses, or rely on light excitation with limited imaging depth. In this work, an ultrasound-induced afterglow (sonoafterglow) nanoprobe is developed to specifically detect granzyme B for accurate imaging of T-cell immunoactivation in vivo. The sonoafterglow nanoprobe (Q-SNAP) consists of sonosensitizers, afterglow substrates, and quenchers. Upon ultrasound irradiation, sonosensitizers generate singlet oxygen, which converts substrates to high-energy dioxetane intermediates that slowly release energy after ultrasound cessation. Due to the proximity, energy from substrates can be transferred to quenchers, leading to afterglow quenching. Only in the presence of granzyme B, quenchers are liberated from Q-SNAP, resulting in bright afterglow emission with a limit of detection (LOD, 2.1 nm) much lower than most existing fluorescent probes. Due to the deep-tissue-penetrating ultrasound, sonoafterglow can be induced through a tissue of 4 cm thickness. Based on the correlation between sonoafterglow and granzyme B, Q-SNAP not only distinguishes autoimmune hepatitis from healthy liver as early as 4 h after probe injection, but also effectively monitors the cyclosporin-A-mediated reversal of T-cell hyperactivation. Q-SNAP thus offers the possibilities of dynamic monitoring of T-cell dysfunction and evaluation of prophylactic immunotherapy in deep-seated lesions.